Sakralisasi Ruang Dan Nilai Tradisi Meburu Di Desa Adat Panjer - Pranajaya, I Kadek; Pertiwi, Putu Ratih; Winarya Prabawa, I Wayan Sukma (Jurnal Penelitian Agama Hindu, 2023)
Bali is very rich with traditions that contain local wisdom values. The tradition in Bali is still preserved until now. This tradition has a strong foundation because it is supported by the beliefs and beliefs of Balinese Hinduism, one of which is the meburu tradition can be trusted to neutralize the influence of negative energy into strength and positive energy. The meburu tradition is a means of purifying Bhuana Alit and Bhuana Agung to be balanced between humans, nature and their environment, both in the sekala realm and in the niskala realms. At present, there are still many people who do not know about the phenomenon created by the concept of sacred space that forms traditions, unique rituals, and the magic of meburu carried out by the people of Panjer Traditional Village. What is the real meaning that can be found from every procession behind all the ritual thoughts, structures, and beliefs that have been carried out continuously so far. This study aims to explore and examine the social values, cultural values, and religious values contained in the meburu tradition, and analyze the implications of the values contained therein. The method used in this study is a qualitative exploration with theological, historical and philosophical approaches. The results of the study found that the series of meburu traditions began with making ceremonial offerings, Ida Bhatara heading to paum/meetings at Bale Agung Temple, melasti, ngembang, meprani, tawur agung panca sata, meburu tradition, and penyimpenan. The foundation in mythology has become a strong foundation in carrying out the religious beliefs of the Panjer Traditional Village community so that the existence of the meburu tradition can remain stable because it is packaged into mythical beliefs. The meburu tradition can maintain cultural values, social values, and religious values that have been passed down from generation to generation in the past to the present so that they remain stable and sustainable. Preserving the meburu tradition can have implications for Hindu devotion, attitudes and ethics, as well as implications for togetherness and cooperation, religious behavior and ethics.